Critical care nurses' knowledge, attitudes, and practices of pressure injury prevention in China: A multicentric cross‐sectional survey. Issue 2 (30th July 2022) - Li, Jiamin; Zhu, Chen; Liu, Ying; Li, Zhaoyu; Sun, Xiangyu; Bai, Yunfeng; Song, Baoyun; Jin, Jingfen; Liu, Yilan; Wen, Xianxiu; Cheng, Shouzhen; Wu, Xinjuan
Abstract: Pressure injury is a serious and preventable problem in intensive care units. Translating guidelines into clinical practice can reduce the incidence of pressure injury. Identifying clinical status, barriers and facilitators contribute to guideline implementation. To identify the knowledge, attitudes, and practices of pressure injury prevention in Chinese critical care nurses. Secondary data were extracted from a multicentric clinical trial. Knowledge and attitudes toward pressure injury prevention were assessed by a fourteen‐item questionnaire. The observed practices were recorded using a case report form. The report complies with the STROBE statement. A total of 950 critical care nurses in 15 hospitals from six provinces of China were investigated. A total of 53.1% of nurses received a median score of 6 points or less. Knowledge regarding the repositioning procedure, risk assessment, and heel pressure injury prevention was insufficient. Over 99% of nurses strongly or somewhat agreed that pressure injury prevention was very important and that they were willing to take measures to prevent pressure injury. A total of 27 781 patient days of pressure injury prevention practice were recorded. Repositioning was the most commonly used prevention measure, followed by support surfaces and prophylactic dressings. A combination of repositioning, support surface, and prophylactic dressing was lacking. Chinese critical nurses showed a low level of knowledge and a positive attitude toward pressure injury prevention. Practices of pressure injury prevention were unsatisfactory. There is a clear gap between the guidelines and clinical practices. The barrier (low‐level knowledge) and facilitator (positive attitude) were identified in this study. According to these findings, strategies need to be developed to promote guideline implementation.